Role of Brick Tea Trade in the Formation of the Unitary Multi-Ethnic Country of China - Liu, Zhiyang (International journal of business anthropology, 2023)
In the Chinese history, no commodity has had a greater impact upon both China and the world other than tea. In the formation of the unitary multi-ethnic country of China, the brick tea trade ran through every stage of the country’s history since the Tang and Song Dynasties as a commercial activity through which the Central Plains dynasties exchanged tea from the Han regions for horses and other commodities from nomads in the northern grasslands and Qinghai-Tibet Plateau. Throughout the trick tea trade that continued for one thousand years, all ethnic groups were involved, consciously or passively, in the production, processing, transport and marketing of the tea, and collaborated in all trading chains and links, thus creating the largest trading activity in the history of China or even the world and exerting a significant influence on the formation of the unitary multi-ethnic country of China as a result.